Draft genome of Gemmata massiliana sp. nov, a water-borne Planctomycetes species exhibiting two variants. Issue 1 (December 2015) - Aghnatios, Rita; Cayrou, Caroline; Garibal, Marc; Robert, Catherine; Azza, Said; Raoult, Didier; Drancourt, Michel
Abstract Gemmata massiliana is a newPlanctomycetes bacterium isolated from a hospital water network in France, using a new culture medium. It is an aerobic microorganism with optimal growth at pH 8, at 30 °C and salinity ≤ 1.25 % NaCl.G. massiliana is resistant to β-lactam antibiotics, due to lack of peptidoglycan in its cell wall.G. massiliana shares a 97 % 16S rRNA gene sequence similarity with the nearest species, Gemmata obscuriglobus; and 99 % similarity with unnamed soil isolates. Its 9, 249, 437-bp genome consists in one chromosome and no detectable plasmid and has a 64.07 % G + C content, 32.94 % of genes encoding for hypothetical proteins. The genome contains an incomplete 19.6-kb phage sequence, 26 CRISPRs, 3 CAS and 15 clusters of secondary metabolites.G. massiliana genome increases knowledge of a poorly known world of bacteria.